The challenges of implementing Project-Based Learning in English medium school - Batysheva, G.A.; Kitibayeva, A.K. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Project-Based Learning is a student-centered approach used to assist in developing learners’ collaboration, communication, and critical thinking skills. Although there are great deals of benefits of this approach, the implementers struggle with the existence of challenges. This study aims to explore the challenges of implementing Project-Based Learning in one of the English medium schools in Kazakhstan. As a result, teachers’ perceptions of PBL and ways of overcoming difficulties were investigated. The participants were teachers with extensive experience in implementing PBL in English medium schools. Data was collected through qualitative method and techniques, including oral and written interviews, which were analyzed to identify teachers’ perceptions of their roles in PBL. Moreover, the way of these issues was questioned to succeed. The findings of the study demonstrated that there are several challenges of PBL, such as lack of experience, time, and language acquisition. In addition, PBL is used as a tool for assisting in gaining some skills for the teachers and learners.
Ағылшын тіліндегі орта мектепте жобалық оқытуды жүзеге асырудың қиындықтары
Проблемы реализации проектного обучения в английской средней школе
Keywords: Project-Based Learning; challenges; EFL teachers; teacher’s role; perception; implementation; English medium school; contemporary methods